Online@AsiaPacific : mobile, social and locative media in the Asia-Pacific - Hjorth, Larissa. (Asia.com ;, 2013)
"Media across the Asia-Pacific region are at once social, locative and mobile. Social in that these media facilitate public and interpersonal interaction, locative in that this social communication is geographically placed, and mobile in so much as the media is ever-present. The Asia-Pacific region has been pivotal in the production, shaping and consumption of personal new media technologies and through social and mobile media we can see emerging certain types of personal politics that are inflected by the local. The six case studies which inform this book: Seoul, Tokyo, Shanghai, Manila, Singapore and Melbourne, offer a range of economic, socio-cultural, linguistic and religious differences, enabling the authors to provide new insights into specific issues pertaining to mobile media in each city. These include social, mobile and locative media as a form of crisis management in post 3/11 Tokyo; generational shifts in Shanghai; political discussion and the shifting social fabric in Singapore; and the erosion of public and private, and work and leisure paradigms in Melbourne. Through its striking case studies, this book sheds new light on how the region and its contested and multiple identities are evolving, and concludes by revealing the impact of mobile media on how place is shaped, as well as shaping, practices of mobility, intimacy and a sense of belonging"--Provided by publisher.